2006
DOI: 10.1002/hup.770
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and tolerability of reboxetine and venlafaxine XR in major depression and major depression with anxiety features: an open label study

Abstract: We may suggest that reboxetine is as effective and tolerable as venlafaxine XR in the treatment of MDD and MDD with anxiety features, and it may be considered a treatment option to venlafaxine XR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A meta-analysis of 10 RCTS of anxious depression found that response rates were slightly greater following SSRI than bupropion treatment for both depression (65.4% vs. 59.4%; NNT 17) and anxiety (61.5% vs. 54.5%; NNT 14) (Papakostas et al, 2008). Thus, if anxiety does impair outcomes of antidepressant treatment, there are few indications that one type of antidepressant is notably more effective than another, and the NNTs of those differences found are of small clinical relevance in most circumstances (Akkaya et al, 2006; Sir et al, 2005). An exception may be OCD, where an RCT in patients with comorbid depression found sertraline was more effective than desipramine (NNT 7–8) in treating both depressive and OCD symptoms (Hoehn-Saric et al, 2000).…”
Section: Acute Treatmentmentioning
confidence: 99%
“…A meta-analysis of 10 RCTS of anxious depression found that response rates were slightly greater following SSRI than bupropion treatment for both depression (65.4% vs. 59.4%; NNT 17) and anxiety (61.5% vs. 54.5%; NNT 14) (Papakostas et al, 2008). Thus, if anxiety does impair outcomes of antidepressant treatment, there are few indications that one type of antidepressant is notably more effective than another, and the NNTs of those differences found are of small clinical relevance in most circumstances (Akkaya et al, 2006; Sir et al, 2005). An exception may be OCD, where an RCT in patients with comorbid depression found sertraline was more effective than desipramine (NNT 7–8) in treating both depressive and OCD symptoms (Hoehn-Saric et al, 2000).…”
Section: Acute Treatmentmentioning
confidence: 99%
“…Anxious depression is defined as a primary diagnosis of major depressive disorder (MDD) with significant symptoms of anxiety Wiethoff et al, 2010). The prevalence of anxious depression was approximately 50% in 2876 patients with MDD enrolled in the sequenced treatment alternatives to relieve depression (STAR*D) project (Fava et al, 2008) and ranged from approximately 40% to 60% of patients in other MDD clinical trial populations (Fava et al, 2000b;Fava et al, 2004;Akkaya et al, 2006;Wiethoff et al, 2010;Seo et al, 2011). Anxious depression is associated with more severe depressive symptoms at baseline compared with nonanxious depression (Fava et al, 2006;Wiethoff et al, 2010) and also with a greater incidence of suicidal ideation and history of suicide attempt, a greater number of previous depressive episodes, and a longer history of illness, after adjusting for severity of depression (Fava et al, 2006;Fava et al, 2008;Wiethoff et al, 2010;Seo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Poelinger and Haber (1989) found anxiety ratings decreased more with maprotiline (noradrenaline selective agent) than with fluoxetine (serotonin selective agent). Akkaya et al (2006) reported that response rate for anxiety of reboxetine (noradrenaline selective agent) group was significantly higher than venlafaxine groups in the middle of treatment in patients with anxious depression, though the final response rate for anxiety was not significantly different. These findings and the present results suggest that the noradrenergic system in brain play a role in improvement of anxious symptoms of depression, and its genetic polymorphisms might affect the onset of therapeutic efficacy of milnacipran for anxiety in depression.…”
Section: Discussionmentioning
confidence: 99%